On deep history and the brain - Smail, Daniel Lord (Ahmanson Foundation book in the humanities., 2008)
When does history begin? What characterizes it? This book dissolves the logic of a beginning based on writing, civilization, or historical consciousness and offers a model for a history that escapes the continuing grip of the Judeo-Christian time frame. It lays out a new case for bringing neuroscience and neurobiology into the realm of history.